Stakeholder engagement in place branding for international talent attraction - Tahvanainen, Anni (2023)
The purpose of the research is to find a solution for the decreasing population number in South Karelia. As the birth rate is decreasing, population ages, and people centralize to growth centers, there is a growing lack of workforce and taxpayers in many developed countries but especially in regions like South Karelia. The objective of this study is to investigate how the public and private sectors are engaged to build a place brand which is attractive for international talent. The theoretical part opens the place brand building process elements, defines stakeholders, their roles, and what are the drivers and inhibitors for place brand engagement. Lastly, it examines the literature delimiting the concept of place branding to international talent attraction. The empirical part of the research uses qualitative research method. Data analysis is based on15 semi-structured interviews from the South Karelian public and private sectors’ preventatives in managerial and specializing positions. The findings show that since the South Karelian brand is not completely unified and needs clarification, the place needs top-down approach and the public sector has significantly bigger role compared to the private sector in South Karelia. The biggest pull factors for the region are LUT, affordable live expenses, and Saimaa and nature. Biggest push factors for the region are lack of employment and career opportunities and lack of activities for young adults. Tutkimuksen tarkoituksena on löytää ratkaisu väestömäärän vähenemiseen Etelä-Karjalassa. Syntyvyyden pienentyessä, väestön ikääntyessä ja väestön keskittyessä kasvukeskuksiin työvoima- ja veronmaksajapula kasvaa monissa kehittyneissä maissa, mutta erityisesti Etelä-Karjalan kaltaisilla alueilla. Tämän tutkimuksen tavoitteena on tutkia, miten julkinen ja yksityinen sektori ovat sitoutuneet rakentamaan paikkabrändin, joka on houkutteleva kansainväliselle lahjakkuudelle. Teoreettinen osio käy läpi paikkabrändin rakennusprosessielementtejä, määrittelee sidosryhmät, niiden roolit ...